2005
DOI: 10.1101/gad.1284005
|View full text |Cite
|
Sign up to set email alerts
|

Histone methyltransferases G9a and GLP form heteromeric complexes and are both crucial for methylation of euchromatin at H3-K9

Abstract: Histone H3 Lys 9 (H3-K9) methylation is a crucial epigenetic mark for transcriptional silencing. G9a is the major mammalian H3-K9 methyltransferase that targets euchromatic regions and is essential for murine embryogenesis. There is a single G9a-related methyltransferase in mammals, called GLP/Eu-HMTase1. Here we show that GLP is also important for H3-K9 methylation of mouse euchromatin. GLP-deficiency led to embryonic lethality, a severe reduction of H3-K9 mono-and dimethylation, the induction of Mage-a gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
777
4
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 732 publications
(828 citation statements)
references
References 41 publications
46
777
4
1
Order By: Relevance
“…These data suggest that reduction of diMe-H3K9 levels at CG-X antigen gene promoters may be necessary but not sufficient for CG-X antigen gene expression, and also imply that DNMT1 and DNMT3b can independently facilitate H3K9 dimethylation at CG-X antigen gene promoters. It is plausible that the euchromatic histone methyltransferases G9a or GLP catalyse H3K9 methylation at CG-X antigen promoter loci in human cancer cells, because G9aÀ/À and GLPÀ/ À mouse embryonic cells each show enhanced expression of MAGE-A genes (Tachibana et al, 2002(Tachibana et al, , 2005. Furthermore, we have recently found that DNMT1 physically interacts with G9a in human cells (unpublished observations), which could provide a mechanism for communication between H3K9 dimethylation, CG-X antigen repression, and CG-X gene promoter DNA methylation.…”
Section: Ac-k9mentioning
confidence: 99%
“…These data suggest that reduction of diMe-H3K9 levels at CG-X antigen gene promoters may be necessary but not sufficient for CG-X antigen gene expression, and also imply that DNMT1 and DNMT3b can independently facilitate H3K9 dimethylation at CG-X antigen gene promoters. It is plausible that the euchromatic histone methyltransferases G9a or GLP catalyse H3K9 methylation at CG-X antigen promoter loci in human cancer cells, because G9aÀ/À and GLPÀ/ À mouse embryonic cells each show enhanced expression of MAGE-A genes (Tachibana et al, 2002(Tachibana et al, , 2005. Furthermore, we have recently found that DNMT1 physically interacts with G9a in human cells (unpublished observations), which could provide a mechanism for communication between H3K9 dimethylation, CG-X antigen repression, and CG-X gene promoter DNA methylation.…”
Section: Ac-k9mentioning
confidence: 99%
“…This isoform involves two open reading frames: NG36 (amino acids 1-209) and G9a (amino acids 210-1210). Isoform-b is a short isoform of G9a dubbed as hG9a(S) and lacks the amino terminal part of isoform-a 19,40 .The mouse G9a (mG9a) is composed of 1229 amino acids, and its composition is closer to isoform-a of human G9a than isoform-b ( Figure 1C). Following co-transfection of H1299 cells with p53 alone or in the presence of hG9a or mG9a with three different reporters (Bax-luc, PUMA-luc and p21-luc) we measured luciferase activity in each case (Fig.…”
Section: Hg9a Induces P53 Transcriptional Activitymentioning
confidence: 99%
“…G9a heterodimerises with G9a-like protein (GLP) via its carboxyl terminal SET domain to exert the full spectrum of its substrate methylation specificity 18,19 . Both proteins (independently and in the complex) catalyse mono-and dimethylation of lysine 9 and lysine 27 of H3 (H3K9 and H3K27, respectively) [20][21][22] and histone H1 isotype 4 (H1.4) (Trojer et al…”
Section: Introductionmentioning
confidence: 99%
“…De plus, de nouvelles données nous permettent d'entreprendre des analyses plus fines et de mieux comprendre les mécanismes épigénétiques responsables du maintien sous silence de ces gènes dans les cellules saines et d'identifier les perturbations épigénétiques se produisant dans les cancers. Par exemple, il a été montré que l'invalidation du gène G9a, ou du gène Glp/Eu-HMTase1, codant pour des méthyltransférases de la lysine 9 (K9) de l'histone H3, aboutit à une expression ectopique des gènes Mage [26,27]. Une analyse plus fine a permis de montrer qu'une mono-méthylation de K9, induite par l'expression d'un mutant de G9a dans les cellules G9a -/-est suffisante pour réprimer l'expression du gène Mage-A [28].…”
Section: Activation Aberrante Des Facteurs C/t Un Indicateur Des Anounclassified